Dielectric Characterization of XAl2O4 (X = Mg, Zn, Ni) Spinel Ceramics - Azam, M.; Atiq, S.; Mustafa, G. M.; Riaz, S.; Naseem, S. (The Nucleus, 2015)
Spherical nanoparticles of XAl2O4 (X = Mg, Zn, Ni) ceramics with large surface area and finely distributed grains, were successfully synthesized by sol-gel auto-combustion method. The formation of spinel structure of XAl2O4 nanoparticles was confirmed by X-ray diffraction. Dielectric tangent loss was decreased as the frequency was increased while a slight increase in the dielectric parameters was observed as the temperature was increased, mainly due to the thermally activated charge carriers. The behavior of real and imaginary parts of impedance has also been discussed which confirms the results from the tangent loss plot. Energy dispersive Xray spectroscopy gives the true stoichiometric at% and wt% contents of various elements present in the samples. The grain size of the synthesized sample range from 20-70 nm and were obtained when the samples were sintered at 900 ÂºC for 4 hrs.